When Sharing Isn’t Caring: The Influence of Seeking The Best on Sharing Favorable Word of Mouth about Unsatisfactory Purchases - Olson, Nicholas J; Ahluwalia, Rohini (Journal of Consumer Research, 2021)
Past research generally finds that if consumers share word of mouth about past purchases with others, the valence of the information tends to be congruent with actual perceptions. Thus, a negative purchase experience should elicit negative (vs. positive) word of mouth. We examine how a goal of attaining the best possible outcome, or maximizing, may alter this tendency. Drawing on prior work demonstrating that consumers may view their own personal failures more favorably through relative comparisons with others faring similarly or worse, we show that maximizing increases consumers’ propensity to share favorable word of mouth about unsatisfactory purchases, in an effort to encourage others to make the same poor choices, as they seek to enhance the perceived relative standing of and post-purchase feelings toward their own unsatisfying outcomes. We further show that consumers particularly exhibit this behavior when sharing with psychologically close (vs. distant) others, as comparisons with close others are especially relevant to relative standing. Finally, we consider the downstream consequences of such behavior, finding that when consumers successfully persuade close others to make the same bad decisions, they feel better about their own outcomes, but are also burdened with feelings of guilt that erode their overall wellbeing.